Human hair growth in vitro: a model for the study of hair follicle biology - Philpott, M P; Sanders, D; Westgate, G E; Kealey, T (Journal of dermatological science, 1994)
The factors that regulate hair follicle growth are still poorly understood. In vitro models may be useful in elucidating some aspects of hair follicle biology. We have developed an in vitro human hair growth model that enables us to maintain isolated human hair follicles for up to 10 days, during which time they continue to grow at an in vivo rate producing a keratinised hair fibre. We have shown that epidermal growth factor (EGF) in our system mimics the in vivo depilatory action of EGF in sheep, and suggest that this occurs as a result of EGF stimulating outer root sheath (ORS) cell proliferation which results in the disruption of normal mechanisms of cell-cell interaction in the hair follicle. We identify transforming growth factor-beta (TGF-beta) as a possible negative regulator of hair follicle growth and show that physiological levels of insulin-like growth factor-I (IGF-I) can support the same rates of hair follicle growth as supraphysiological levels of insulin. Furthermore, in the absence of insulin hair follicles show premature entry into a catagen-like state. This is prevented by physiological levels of IGF-I. Finally we demonstrate that the hair follicle is an aerobic glycolytic, glutaminolytic tissue and discuss the possible implications of this metabolism.